Multimodal treatment with Neoadjuvant chemotherapy for eyelid and periocular sebaceous gland carcinoma: Long-term outcomes - Vijitha S. Vempuluru; Anshika Luthra; Vijay Anand Reddy Palkonda; Swathi Kaliki (American Journal of Ophthalmology Case Reports)
Purpose: To report the long-term outcomes of multimodal treatment with intravenous cisplatin and 5-fluorouracil-based neoadjuvant chemotherapy (NACT) for advanced eyelid and periocular sebaceous gland carcinoma (eSGC). Observations: Three patients of eSGC with 10-year follow-up were reviewed. The mean age at presentation of eSGC was 50 years (median, 50 years; range, 41–59 years). The lower eyelid was the tumor epicenter in two (66 %) patients and the medial canthus in one (33 %) patient. The mean tumor basal diameter was 27 mm (median, 30 mm, range, 20–30 mm). Orbital extension was present in all patients. By the 8th edition of AJCC classification, tumors belonged to T4aN0M0 in 2 patients and T4aN1M0 in 1 patient. NACT with 5-Fluorouracil and cisplatin was administered in all patients for a mean of 3 cycles (median, 3; range, 2 to 3). The mean percentage of clinical tumor volume reduction after neoadjuvant chemotherapy was 93 % (median, 100 %; range, 80 %–100 %). Three months after NACT, two patients underwent excisional biopsy of residual tumor, all 3 underwent external beam radiotherapy to the orbit and adjuvant systemic chemotherapy, and 1 with lymph node metastasis at presentation received EBRT to the lymph node area. At a mean follow-up period of 11 years (median, 11 years; range, 10–11 years) after NACT initiation, tumor control, life salvage, and globe salvage were achieved in all patients. No events of tumor recurrence, metastasis, or death were noted. Conclusions and importance: The long-term outcomes in patients with eyelid and periocular SGC who achieve tumor control with platinum-based NACT seem promising.